Clinico-radiological and pathological correlation of interstitial lung diseases: a prospective single centre study - Nair, Ankita Dhiman; Thakur, Vijay; Sarkar, Malay (International Journal of Research in Medical Sciences, 2021)
Background: Current investigation was done to study the role of HRCT chest in the diagnosis and characterization of interstitial lung diseases, yield of transbronchial lung biopsy and role of multidisciplinary approach of diagnosis. Methods: We prospectively analyzed clinical features and radiological findings in 38 patients of ILD. Radiological diagnosis on HRCT was made in every case depending on type of predominant abnormality and pattern of involvement. Following this, TBLB was done in every case. Results: ILD was diagnosed in all cases on HRCT. Most common ILD type was UIP (31.5%) followed by sarcoidosis (21%) and NSIP (15.7%). Other ILD subtypes encountered were, RB-ILD, AIP and acute silicosis. In 68.4% cases, there was definitive diagnosis on TBLB. Out of which in 15.7% cases, HRCT and TBLB diagnosis were different. In 15.3% cases, TBLB gave diagnosis of only non- specific ILD. Conclusions: HRCT can detect ILD in 100% cases & can characterize ILD into various patterns. But, HRCT alone without clinical correlation and pathology can cause diagnostic confusion in many cases. However, multidisciplinary approach by engaging clinician, radiologist and pathologist can lead to accurate diagnosis in many cases of ILD. TBLB is a safe, minimally invasive procedure which can establish correct diagnosis in many cases especially in broncho-centric diseases.